Socio-Adaptive Dimension of Students’ Personal Space - Iryna Havryliuk (International Journal of Emerging Issues in Early Childhood Education, 2019)
Psychological literature presents such notions as "living space," "mental image," "psychological space," etc.; however, only a few pieces of research practically view the modal content of students' spatial organization within the limits of their social and adaptive security. Therefore, it is essential to develop empirical programs for studying the modal features of students' personal space in a socio-adaptive dimension. The article aims to introduce and apply conceptual and methodological support for studying the issue mentioned above; explain the psychological content of modal signs of students' personal space in a socio-adaptive dimension. The following methods were used to conduct the research: theoretical (analysis, synthesis, comparison, abstraction, systematization, and generalization); empirical (observation and conversation); mathematical statistics (Kruskal-Wallis H Test). Data were processed using SPSS Statistics software, version 13.0. One hundred fifty-seven students aged 18 to 25 were invited to participate in research. After specifying the study stages, defining strategies and applying various psychodiagnostic methods, the results were as follows: a) Students with a high level of personal space sovereignty (45.9 % of testees) demonstrated profound control over life; it indicates excellent socio-psychological adaptation and mental well-being of an individual, combined with high standards of autonomy and self-identity; b) Students with a medium sovereignty level (38.2 % of testees) expressed an uncertain position related to determining their personal space. It is often associated with social factors of an individual's self-realization, which impede and even destroy the potential establishment of a holistic, full-fledged own space; c) Students with a low level of psychological space sovereignty (15.9 % of testees) showed the signs of deprivation; such young people might experience alienation and fragmentation of their own life, complications in the search for the object of identification.